Reassortant Cache Valley Virus Associated With Acute Febrile, Nonneurologic Illness, Missouri - Baker, Molly; Hughes, Holly R; Naqvi, S Hasan; Yates, Karen; Velez, Jason O; McGuirk, Sophia; Schroder, Barb; Lambert, Amy J; Kosoy, Olga I; Pue, Howard; Turabelidze, George; Staples, J Erin (Clinical infectious diseases, 2021)
An adult male from Missouri sought care for fever, fatigue, and gastrointestinal symptoms. He had leukopenia and thrombocytopenia and was treated for a presumed tickborne illness. His condition deteriorated with respiratory and renal failure, lactic acidosis, and hypotension. Next-generation sequencing and phylogenetic analysis identified a reassortant Cache Valley virus.